A bibliometric analysis of the research hotspots and frontiers related to cell death in spinal cord injury - He, Kelin; Yu, Han; Zhang, Jieqi; Wu, Lei; Han, Dexiong; Ma, Ruijie (Frontiers in Neurology, 2024)
Background: Spinal cord injury (SCI) is a severe central nervous trauma that can cause serious consequences. Cell death is emerging as a common pathogenesis after SCI. In the last two decades, numerous studies have been published in the field of cell death after SCI. However, it is still rare to find relevant bibliometric analyses. This bibliometric study aims to visually represent global research trends in the field of cell death after SCI. Methods: Bibliometric data were sourced from the Web of Science Core Collection (WoSCC) database. VOSviewer, CiteSpace, and R software (“bibliometrix” package) were used to analyze and visualize bibliometric data. Annual scientific production, countries/regions, institutions, authors, journals, highly cited papers, keywords, and literature co-citation were evaluated to determine research performance. Results: An analysis of 5078 publications extracted from the WoSCC database revealed a fluctuating yet persistent growth in the field of cell death after SCI over the past 23 years. China and the United States, contributing 69% of the total publications, were the main driving force in this field. The Wenzhou Medical University from China contributed to the most papers. In terms of authors, Salvatore Cuzzocrea from the University of Messina had the highest number of publications. The “Journal of Neurotrauma” was the top journal in terms of the number of publications, however, the “Journal of Neuroscience” was the top journal in terms of the number of citations. The theme of the highly cited articles mainly focused on the mechanism of cell death after SCI. The keyword and literature co-citation analysis mainly focused on the mode of cell death, mechanism research of cell death, and functional recovery after SCI. Conclusion: This study analyzes the research hotspots, frontiers, and development trends in the field of cell death after SCI, which is important for future studies.